Measuring deviant sexual interest using the emotional stroop task - Price, Shelley A. (Criminal justice and behavior, 2013)
The emotional Stroop task has been used to assess deviant sexual interests of sexual abusers. Two limitations noted in the literature are difficulties surrounding the choice of word stimuli and the task?s inability to elicit significant differences between offender subtypes thus far. The purpose of this study was to examine differences in emotional Stroop bias between three adult groups using new, empirically derived word stimuli intended to reflect sexual interests more specific to sexual abusers. Significant differences were found between sexual abusers and nonoffending controls for affective and sexual word stimuli. The results further support differential processing biases between sexual offenders and nonoffenders; however, difficulties in differentiating between offender groups are still evident. Implications of these findings are discussed and recommendations for future research are made.